Is zero leverage good for firms’ performance? - Morais, F.; Serrasqueiro, Z.; Ramalho, J.J.S. (The European Journal of Finance, 2025)
This paper examines the effect of zero-leverage policies on firms’ financial performance, distinguishing between firms that are debt-free by their own choice (financially unconstrained firms) or as a result of financial constraints (financially constrained firms). Using an international sample of European and US listed firms for the 1990–2022 period, we find that the effect of zero leverage on firms’ performance is particularly beneficial for financially unconstrained firms: (i) zero leverage influences their long-term market performance positively, which is boosted during crisis periods; and (ii) it does not influence their short-term performance in non-crisis years, although it affects it positively during crisis periods. In contrast, most of our models suggest that zero leverage has no significant impact on the performance of financially constrained firms, especially in the short term.